. Role of cooperative farming in development of agricultural production in Armenia - Бадалян, М. Э.; Казарян, А. Р.; Маргаряан, М. А. (Scientific Progress & Innovations, 2012)
In highly developed countries cooperatives play an important role in the development of agriculture. The cooperatives promote efficient use of resources, increasing production efficiency. This process goes slowly yet in Armenia due to the imperfection of the legal field, the low level of government assistance and other factors. Tо accelerate the process of formation of agricultural cooperatives it is necessary to set up a positive environment, to pass a law «About cooperatives» and governmental complex assistance program, to compensate all or part of expenses associated with the creation of cooperatives.